ANALYSIS OF DIFFICULTIES OF LEARNING ARABIC LANGUAGE IN LANGUAGE INTENSIVE PROGRAM OF SMP NURUL JADID (LIPS) PAITON PROBOLINGGO - Hidayati, Khusnul; Wijaya, Mualim (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study analyses difficulties in learning Arabic at the Language IntensifProgram Of SMP Nurul Jadid (LIPS) Paiton Probolinggo. It aims to determine thecontext of language learning difficulties and the efforts made to overcome difficultiesin learning Arabic at (LIPS) Paiton Probolinggo. This type of research is qualitativeresearch. The research subjects were chaperones (ustadzah) and students, usingobservation, interview, and documentation data collection methods. The study resultsshow that the difficulties in learning Arabic at LIPS are: holding back speakingArabic, having difficulty writing (making instal), and grammar rules (nahwu-sarf),while efforts to overcome them are by habituation, both in speaking and writinglanguage Arabic